Pembangunan Tools Pembelajaran Pemrograman Java Melalui Live CD / Live USB - Irwan Adi Pribadi; Wamiliana Wamiliana; Ervan Heppyda; Wisnu Wardhana (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2015)
Linux is an open source operating system. Everyone can change and develop the Linux operating system as needed. In this research we use Linux operating system to generate a new operating system that supports learning Java programming. The resulting operating system is runs via Live CD / Live USB. The operating system has been successfully created and can be used as learning tools for Java programming.